2005
DOI: 10.1021/tx049677g
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Degradation of Microcystins and Nodularin

Abstract: Microcystins and nodularins produced by cyanobacteria are potent hepatotoxins and tumor promoters. They are, respectively, cyclic heptapeptides and cyclic pentapeptides containing a characteristic beta-amino acid residue, (2S,3S,8S,9S)-3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4(E ),6(E)-dienoic acid (Adda). Strain B-9 isolated from Lake Tsukui, Japan, degrades microcystin-LR, which is the most toxic among the microcystins, to nontoxic Adda as an end product. In the present study, we characterized the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 21 publications
8
99
0
4
Order By: Relevance
“…Adda is a characteristic β-amino acid (2S, 3S, 8S, 9S)-3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4(E), 6(E)-dienoic acid, which is essential to the toxicity of MC-RR. Previous studies revealed that Adda-Arg was the bond that was easily attacked during the enzymatic degradation by many bacteria (Bourne et al, 1996(Bourne et al, , 2001Imanishi et al, 2005). Ion with m/z 1056.9 may thus be derived from MC-RR by opening the ring through breaking the Adda-Arg bond and combining one hydrogen on the NH 2 group of Adda and a hydroxyl on the carboxyl group of arginine.…”
Section: Enzymatic Degradation Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Adda is a characteristic β-amino acid (2S, 3S, 8S, 9S)-3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4(E), 6(E)-dienoic acid, which is essential to the toxicity of MC-RR. Previous studies revealed that Adda-Arg was the bond that was easily attacked during the enzymatic degradation by many bacteria (Bourne et al, 1996(Bourne et al, , 2001Imanishi et al, 2005). Ion with m/z 1056.9 may thus be derived from MC-RR by opening the ring through breaking the Adda-Arg bond and combining one hydrogen on the NH 2 group of Adda and a hydroxyl on the carboxyl group of arginine.…”
Section: Enzymatic Degradation Pathwaymentioning
confidence: 99%
“…The tetrapeptide was finally degraded into Adda (Imanishi et al, 2005). The MC-RR biodegradation pathways by Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…B-9 is a bacterial strain isolated from a eutrophicated lake and belongs to Sphingosinicella sp., which can hydrolyze MCs and nodularin using its intracellular enzymes. 3 An earlier study was carried out to investigate further the hydrolytic capabilities of the MC-degrading enzymes of B-9. 13 As a result of this investigation, it was confirmed that the enzymes can also hydrolyze the peptide bonds of several cyanobacterial cyclic peptides that were structurally different from the MCs and nodularin.…”
Section: Microbial Degradation Of Cyclic Peptides H Kato Et Almentioning
confidence: 99%
“…2 This strain showed a promising potential for the degradation of MC-related compounds and nodularin. 3 Such an MC-degrading bacterium was first isolated in Australia and was identified as one of the Sphingomonas strains (ACM-3962) in 1994. 4 Phenotypically, similar bacteria capable of degrading MC have been reported subsequently all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…and Bacillus sp., have been regarded as excellent candidates for microcystindegrading properties [8][9][10][11]. In contract to several chemical treatments, biodegradation methods not only avoid producing carcinogenic substances and other mutagens, but also effectively remove microcystins [12].…”
Section: Introductionmentioning
confidence: 99%